Predicting the effective depth of soil stabilization for marine clay treated by biomass silica - Lim, Jing Jin; Mohd Yunus, Nor Zurairahetty; Hezmi, Muhammad Azril; Abdul Rashid, Ahmad Safuan; Marto, Amination; Kalatehjari, Roohollah; Pakir, Faizal; Mashros, Nordiana; Adekunle Ganiyu, Abideen (Springer Nature, 2018)
Reclamation and development towards the oceanic area had become a trend of modern days, where the marine soil need to be treated prior construction. The increase in unconfined compressive strength of marine clay treated by Biomass Silica, ‘SH-85’ has been demonstrated by several investigations. This paper studies the stress-strain behavior of marine clay treated with 12% of SH-85 with different curing periods and confining pressures. The results show that the strength parameters of the stabilized soil are greatly improved during the early stage of the curing period under higher confining pressures. In addition, the XRD analysis and microstructure study confirm the appearance of a new reflection peak at 29° in the treated soils indicating the formation of Calcium Silicate Hydrate (CSH). The curing period of 7 days at a confining pressure of 400 kPa was found to be an optimum combination for in situ stabilization. The effective stabilization depth predicted at each location can be defined as the depth ensuing the mentioned confining pressure. The approach of this research can be applied in construction activities associated with marine clay to help engineers in risk assessment, feasibility study and planning of the developments